Evaluation of Procurement Process on Ethanol Factory Construction – Lampung - Roi Milyardi; Indra Koheru; Cindrawaty Lesmana (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2021)
The procurement process in construction is quite complicated with its various methods. One of them, design and construct contracting, which often used, is one that has an advantage of saving time and money. However, for companies without sufficient capabilities to carry out procurement, the design construct contract method also requires expert assistance in the process. To meet the construction procurement process requirements, one workable solution is that the company collaborates with a university for its factory construction development. The relevant academicians have expertise to solve problems in procurement process. The academician team was collecting appropriate data and then evaluating it to give suggestions on the construction procurement process. The method used was a simple comparison of the price proposed by the contractor to the owner estimate which was then calculated based on the Indonesian Regulation by the Minister of Public Works and Housing no. 28/PRT/M/concerning the unit price analysis that used as reference. Prices for materials, tools, and wages referred from Indonesian unit price journal references. The result of the evaluation was to determine the contract winner based on price and technical design aspects within company budget. During the evaluation process, clarification was made regarding the proposed design, construction method and quality of the proposed material to match the technical aspects of the design. The price evaluation process which was carried out in a short term has assisted the company in carrying out its construction procurement process. In the long run, cooperation can be developed in the form of human resource training so that the company can develop independently in carrying out the construction procurement process. Keywords: construction procurement, community service, owner estimate